SWOT Analysis Of Waterfront City; The Development Concept In Palangka Raya - Syamsuri, Syamsuri; Asmawati, Yunita; Ikat, Satria Adiguna (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
Waterfront City is a concept of structuring and utilizing the area of the riverbank which is used as an area of public space while observing environmental sustainability as well. Palangka Raya city as one of the cities on the banks of the Kahayan River with unspoiled characteristics is a good carrying capacity and strength for the development of the public area. The purpose of this research was to describe and analyze the concept of developing Waterfront City in Palangka Raya City through SWOT analysis. The used of mix methods of qualitative and quantitative found the result of the sphere that needed to be developed. Since the Data of Internal factors (strengths and weaknesses) and external factors (opportunities and threats) denoted certain results through analysis. The results showed that the SWOT analysis of the development concept of Waterfront City in Palangka Raya City had great potential for the future.